2018
DOI: 10.1093/hmg/ddy413
|View full text |Cite
|
Sign up to set email alerts
|

PD-linked CHCHD2 mutations impair CHCHD10 and MICOS complex leading to mitochondria dysfunction

Abstract: Coiled-coil-helix-coiled-coil-helix domain containing protein 2 (CHCHD2) mutations were linked with autosomal dominant Parkinson’s disease (PD) and recently, Alzheimer’s disease/frontotemporal dementia. In the current study, we generated isogenic human embryonic stem cell (hESC) lines harboring PD-associated CHCHD2 mutation R145Q or Q126X via clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein 9 (Cas9) method, aiming to unravel pathophysiologic mechanism and seek potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 58 publications
(73 reference statements)
2
59
0
Order By: Relevance
“…Here, we showed that CHCHD10 is significantly reduced in ALS spinal cord tissues, suggesting that there is a loss of CHCHD10 function at least at the end stage of the disease. This reduction of CHCHD10 may lead to MICOS reduction, abnormal mitochondrial cristae structure and synaptic damage leading to motor neuron death 23 48. It is also worth noting that while CHCHD10 protein expression levels were significantly higher for control samples than ALS cases, there was considerable variation, particularly among control samples (figure 3B and supplementary table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Here, we showed that CHCHD10 is significantly reduced in ALS spinal cord tissues, suggesting that there is a loss of CHCHD10 function at least at the end stage of the disease. This reduction of CHCHD10 may lead to MICOS reduction, abnormal mitochondrial cristae structure and synaptic damage leading to motor neuron death 23 48. It is also worth noting that while CHCHD10 protein expression levels were significantly higher for control samples than ALS cases, there was considerable variation, particularly among control samples (figure 3B and supplementary table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Although CRISPR mediated treatment systems are widely used in both mentioned fatal diseases that are caused by SNPs or in other dangerous and deadly diseases like Parkinson's disease (PD) (Zhou, et al 2018), Duchenne muscular dystrophy (DMD) (Lim, et al 2018) or various cardiovascular diseases, they do have their downsides and limitations that require additional work and research to overcome them.…”
Section: Where Crispr-cas9 Falls Shortmentioning
confidence: 99%
“…As the MICOS complex is reported to interact with OPA1 and with C2/C10 (Ding et al, 2015;Darshi et al, 2011;Genin et al, 2016;Zhou et al, 2019), we tested whether reduction in MICOS subunits could account for the observed OMA1 activation and L-OPA1 cleavage. As expected, depletion of a central subunit of the MICOS complex, MIC60, destabilized MIC19 and MIC27, components of the respective MICOS subcomplexes ( Figure 2D).…”
Section: C2/c10 Double Knockout Leads To Cristae Abnormalities Due Tomentioning
confidence: 99%
“…Although their precise function remains unknown, cristae abnormalities have been observed in muscle tissue and cell lines from patients with C10 mutations, as well as a Drosophila lacking the C2/C10 ortholog (Bannwarth et al, 2014;Ajroud-Driss et al, 2015;Meng et al, 2017). To explain cristae abnormalities in C2/C10 patients, C10 and later C2 were proposed to be structural components of the mitochondrial contact site and cristae organizing system (MICOS) complex (Bannwarth et al, 2014;Genin et al, 2016;Zhou et al, 2019). However, recent reports have challenged this model, suggesting that C2/C10 mutation or loss may lead to cristae abnormalities by another as of yet unidentified mechanism (Straub et al, 2018;Burstein et al, 2018;Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%